Application of Decision Tree Algorithm for Predicting Monthly Pan Evaporation Rate - Abed M.; Imteaz M.A.; Ahmed A.N.; Huang Y.F. (Engineers Australia, 2023)
Correlation methods; Decision trees; Forecasting; Meteorology; Water management; Wind; Decision-tree algorithm; Design models; Evaporation rate; Hydrological models; Input parameter; Irrigation system design; Malaysia; Non-linear phenomenon; Pan evaporation; Waters resources; Evaporation